Role of the Striatum and the Cerebellum in Motor Skill Acquisition - Markus M. Schugens; Caterina Breitenstein; Hermann Ackermann; Irene Daum (Behavioural Neurology)
Motor skill acquisition was investigated in patients with Parkinson's disease (PD) or cerebellar dysfunction using two sensory-guided tracking tasks. The subjects had to learn to track a visual target (a square) on a computer screen by moving a joystick under two different conditions. In the unreversed task, the horizontal target movements were semi-predictable and could be anticipated. In the reversed task, the horizontal movements of a pointer which had to be kept within the target square were mirror-reversed to the joystick movements. PD patients showed intact learning of the semi-predictable task and reduced learning of the mirror-reversed task; patients with cerebellar dysfunction showed the opposite pattern. These findings are discussed in relation to the differential contribution of the cerebellum and the striatum to motor skill acquisition: the cerebellum appears to participate in the implementation of anticipatory movements, whereas the striatum may be critically involved in types of motor learning which require a high degree of internal elaboration.